(untitled) - Graham, Billy; (1918-2018) (U.S.A, 1996)
This book is a topical guide with biblical answers to the urgent concerns of our day. It is a valuable resource for any Christian interested in sharpening his or her skills in using the Bible to share Christ with a needy world.
Keywords: Peer counseling in the church -- Handbooks, manuals, etc